The Destructive Capacity of Drug Abuse: An Overview Exploring the Harmful Potential of Drug Abuse Both to the Individual and to Society. (16th July 2013) - Fox, Thomas Peter; Oliver, Govind; Ellis, Sophie Marie
Abstract : From a public health perspective, substance abuse has long been a source of major concern, both for the individual's health and for wider society as a whole. The UK has the highest rates of recorded illegal drug misuse in the western world. In particular, it has comparatively high rates of heroin and crack cocaine use. Substances that are considered harmful are strictly regulated according to a classification system that takes into account the harms and risks of taking each drug (see the tables) (Nutt et al. (2007)). The adverse effects of drug abuse can be thought of in three parts that together determine the overall harm in taking it: (1) the direct physical harm of the substance to the individual user, (2) the tendency of the drug to induce dependence, and (3) the effect of abuse of the drug on families, communities, and society (Gable (2004, 1993)). In this report, we discuss published evidence relating to the harm of substance misuse and consider the neuropsychopharmacological mechanisms behind addiction in an attempt to gain an improved picture of the potential devastation that abuse of these substances may evoke.